Overview of the coordinated ground-based observations of Titan during the Huygens mission - Witasse, Olivier; Lebreton, J.-P.; Bird, Michael; Dutta-Roy, R.; Folkner, W.; Preston, Robert; Asmar, S.; Gurvits, L.; Pogrebenko, S.; Avruch, I.; Campbell, R.; Bignall, Hayley; et al. (American Geophysical Union, 2006)
Coordinated ground-based observations of Titan were performed around or during the Huygens atmospheric probe mission at Titan on 14 January 2005, connecting the momentary in situ observations by the probe with the synoptic coverage provided by continuing ground-based programs. These observations consisted of three different categories: (1) radio telescope tracking of the Huygens signal at 2040 MHz, (2) observations of the atmosphere and surface of Titan, and (3) attempts to observe radiation emitted during the Huygens Probe entry into Titan's atmosphere. The Probe radio signal was successfully acquired by a network of terrestrial telescopes, recovering a vertical profile of wind speed in Titan's atmosphere from 140 km altitude down to the surface. Ground-based observations brought new information on atmosphere and surface properties of the largest Satumian moon. No positive detection of phenomena associated with the Probe entry was reported. This paper reviews all these measurements and highlights the achieved results. The ground-based observations, both radio and optical, are of fundamental imnortance for the interpretatinn of results from the Huygens mission.